2006
DOI: 10.17528/cifor/002037
|View full text |Cite
|
Sign up to set email alerts
|

Forests and human health: assessing the evidence

Abstract: C e n t e r f o r I n t e r n a t i o n a l F o r e s t r y R e s e a r c h Carol J. Pierce Colfer Douglas Sheil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 214 publications
(250 reference statements)
0
3
0
Order By: Relevance
“…Public forests provide many goods and services that support many lifeforms on the planet. Reviewed studies have demonstrated that forests provide safety nets and gap fillers [23,33], they are sources of bioactive polyphenols [25], have immense pharmacological potential [27] and sources of flavonoid and phenolic acids [30]. However, with escalating global environmental threats, attention is now shifting to the sustainable management of all components of forest ecosystems, and hence deadwood has become an interesting topic of study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public forests provide many goods and services that support many lifeforms on the planet. Reviewed studies have demonstrated that forests provide safety nets and gap fillers [23,33], they are sources of bioactive polyphenols [25], have immense pharmacological potential [27] and sources of flavonoid and phenolic acids [30]. However, with escalating global environmental threats, attention is now shifting to the sustainable management of all components of forest ecosystems, and hence deadwood has become an interesting topic of study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of humans, forests provide compounds that are used in pharmaceuticals and nutraceuticals [24,25]. Mushrooms and various fungi extracted from forests have been found to possess invaluable pharmacological potential [26,27]. In addition, forest food can provide nutrients that people may not have access to and may help people survive famine, war, or drought [28][29][30][31][32].…”
Section: Circular Forest-based Bioeconomy and Deadwood Management Str...mentioning
confidence: 99%
“…These include improvements in environmental quality, such as heat regulation and noise abatement (Hartig et al, 2014), the promotion of physical activity and associated Body Mass Index improvements (Thompson Coon et al, 2011), enhanced social interaction, social inclusion and cohesion and perceived safety (Maas et al, 2009;De Vries et al, 2003), and opportunities for spiritual wellbeing experiences, typically in more remote 'wilderness' green spaces (Warber et al, 2013). Ecosystems such as forests and coral reefs have also been found to play a vital role in providing a source of medicines and pharmaceutical products (Stolton & Dudley, 2009;Colfer et al, 2006), which greatly contribute to human health and well-being.…”
Section: Van Hammentioning
confidence: 99%